Molecular genetic alterations in thyroid transcription factor 1–negative lung adenocarcinoma in cytology specimens: A subset with aggressive behavior and a poor prognosis - Erika F. Rodriguez (2018)
© 2018 American Cancer Society BACKGROUND: Patients with thyroid transcription factor 1 (TTF1)–negative pulmonary adenocarcinoma (ADC) have been reported to have a worse prognosis and to lack epidermal growth factor receptor (EGFR) mutations. This study describes a series of cytology specimens from patients with clinically confirmed pulmonary carcinoma negative for TTF1. METHODS: A search for TTF1-negative ADC from 2010 to 2017 was performed. Each patient’s clinical history, pathology specimens, and molecular results were noted. Two hundred ten patients with TTF1-positive pulmonary ADC formed the control group. RESULTS: Fifty specimens were identified from 50 patients (26 females and 24 males). The median age was 58.5 years. The smoking history was as follows: 38 smokers/former smokers (76%), 10 nonsmokers (20%), and 2 patients with an unknown status (4%). Thirty-nine patients (78%) had no previous history of malignancy. The clinical stages were as follows: stage I or II (n = 2 [4%]), stage III (n = 9 [18%]), stage IV (n = 37 [74%]), and unknown (n = 2 [4%]). Patients’ mean survival was 10.3 months. Molecular results were available in 43 cases. Twenty-seven cases (63%) had no mutation identified; when they were compared with the control group, TTF1-negative patients had overall shorter survival (P =.0047), even though no statistically significant difference was seen on the clinical stage. Known mutations were less frequent (P =.0095) in TTF-negative tumors (KRAS mutations, n = 11 [25%]; anaplastic lymphoma kinase [ALK], n = 3 [7%]; and EGFR, n = 2 [5%]). This was particularly true for EGFR mutations (P =.047). However, ALK rearrangements were present at an increased frequency in the TTF1-negative group (P =.018). CONCLUSIONS: Patients with TTF1-negative lung ADC have worse overall survival, a lower frequency of known mutations, and a higher frequency of ALK alterations.